Bir Tarihçinin Kaleminden Osmanlı Dönemi Gördes Halıcılığı Kitabı - Yazıcı, Ömür (Vakıflar Genel Müdürlüğü, 2014)
Osmanlı Dönemi Gördes Halıcılığı, Yazarı: Doç. Dr. Ertan Gökmen, Celal Bayar Üniversitesi Yayınları, Yayın No: 0013, Manisa 2014, Sayfa Sayısı: 248.

In this issue Ömür Yazıcı presents a new book on Gördes carpets in Ottoman era written by an historian , associate professor Ertan Gökmen.
A Book on Gördes Carpets in Ottoman Period by an Historian